Reflection of Historical Time in Kazakh Documentaries - Nazira R. Mukusheva (Publishing house "Sreda", 2022)
The article deals with the unity of the national cultural heritage and historical time in Kazakh documentary films. The purpose of the article is to analyze the features of the use of time in the depiction of the spiritual world, national customs and traditions in the films of documentary film masters OrazAbishev, BakhytGafu-Kaiyrbekov and others. Based on the formal stylistic method, the significance of historical time in documentary films is explored. The author, considering the unity of the national cultural heritage and historical time in the Kazakh documentary, concludes that in the Kazakh documentary film, the reflection of the unity of the national cultural heritage and historical time has gone through several stages of formation, and was closely connected with the social, political phenomena taking place in the country. In conclusion, the stages of the formation of Kazakh documentary cinema are listed from the point of view of reflecting historical time and it is argued that: 1) the first stage is associated with the establishment of Soviet power in Kazakhstan, with the ideology and politics of socialism (1927-1930); 2) the second stage is connected with the reflection of people's memory and history on the documentary film screen in the conditions of the political, social atmosphere of Kazakhstan in the 1960s (1960-1970); 3) the third stage reflects the processes of returning to the origins of national consciousness, people's historical memory (1990-2020).